Nepenthes mirabilis (Lour.) Druce Planlet at a Various Levels of Murashige & Skoog Medium Density In Vitro - Nadia Fakhriyati Arfa; Endang Nurcahyani; Zulkifli Zulkifli; Tundjung Tripeni Handayani (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
This study aims to determine the variation of the stomata index of the Kantong Semar (Nepenthes mirabilis) planlet at a various medium density of the Murashige and Skoog. This study used a Completely Randomized Design using one factor (medium density of the Murashige and Skoog). We used 5 levels of medium density, i.e.: 1/16 MS, 1/8 MS, 1/4 MS, 1/2 MS, and MS. Homogeneity test used Levene’s test of 5% significance level, then analysis of variance is carried out at 5% significance level and followed by Tukey test at 5% significance level. The results showed that the lower the level of Murashige and Skoog medium density on the Nepenthes mirabilis plantlet, the stomata index also increased.